Courses
Courses for Kids
Free study material
Free LIVE classes
More LIVE
Join Vedantu’s FREE Mastercalss

# $\alpha ,\beta$ are complex cube roots of unity and $x=a+b$, $y=a\alpha +b\beta$, $z=a\beta +b\alpha$ then ${{x}^{3}}+{{y}^{3}}+{{z}^{3}}$=A. $0$B. $3ab$C. $3({{a}^{3}}-{{b}^{3}})$D. $3{{(a-b)}^{3}}$ Verified
363.9k+ views
Hint: Assume $\alpha =\omega ,\beta ={{\omega }^{2}}$. Substitute the values in $x.y$and $z$. Then add $x+y+z$ and simplify. Then use the formula ${{x}^{3}}+{{y}^{3}}+{{z}^{3}}=(x+y+z)({{x}^{2}}+{{y}^{2}}+{{z}^{2}}-xy-yz-zx)+3xyz$. Then substitute the value of $x+y+z$ in the formula. You will get the answer. Try it.

$x=a+b$
$y=a\omega +b{{\omega }^{2}}$
$z=a{{\omega }^{2}}+b\omega$

So $x+y+z=a+b+a\omega +b{{\omega }^{2}}+a{{\omega }^{2}}+b\omega$
$x+y+z=a(1+\omega +{{\omega }^{2}})+b(1+\omega +{{\omega }^{2}})$

We know $1+\omega +{{\omega }^{2}}=0$.
$x+y+z=0$

We know the formula ${{x}^{3}}+{{y}^{3}}+{{z}^{3}}=(x+y+z)({{x}^{2}}+{{y}^{2}}+{{z}^{2}}-xy-yz-zx)+3xyz$.
So here$x+y+z=0$.

So ${{x}^{3}}+{{y}^{3}}+{{z}^{3}}=(0)({{x}^{2}}+{{y}^{2}}+{{z}^{2}}-xy-yz-zx)+3xyz$
${{x}^{3}}+{{y}^{3}}+{{z}^{3}}=3xyz$
So we know the value of$x,y$ and $z$.

So substituting the values we get,
${{x}^{3}}+{{y}^{3}}+{{z}^{3}}=3(a+b)(a\omega +b{{\omega }^{2}})(a{{\omega }^{2}}+b\omega )$
Simplifying we get,
\begin{align} & {{x}^{3}}+{{y}^{3}}+{{z}^{3}}=3(a+b)({{a}^{2}}{{\omega }^{3}}+ab{{\omega }^{3}}+ab{{\omega }^{4}}+{{b}^{2}}{{\omega }^{3}}) \\ & {{x}^{3}}+{{y}^{3}}+{{z}^{3}}=3({{a}^{3}}+{{b}^{3}}) \\ \end{align}
${{x}^{3}}+{{y}^{3}}+{{z}^{3}}=3({{a}^{3}}+{{b}^{3}})$

So we get the value of ${{x}^{3}}+{{y}^{3}}+{{z}^{3}}=3({{a}^{3}}+{{b}^{3}})$.

Note: Read the question carefully. Also, while simplifying, don't make any mistake. Take utmost care of the sign. Do not jumble while simplifying. Solve it step by step. You must know the formula ${{x}^{3}}+{{y}^{3}}+{{z}^{3}}=(x+y+z)({{x}^{2}}+{{y}^{2}}+{{z}^{2}}-xy-yz-zx)+3xyz$.

Last updated date: 03rd Oct 2023
Total views: 363.9k
Views today: 6.63k